Research on Heat Source Model and Weld Profile for Fiber Laser Welding of A304 Stainless Steel Thin Sheet. (22nd April 2018) - Li, Peizhi; Fan, Yu; Zhang, Chonghao; Zhu, Zhiyuan; Tian, Wenteng; Liu, Anmin
Abstract : A heat source model is the key issue for laser welding simulation. The Gaussian heat source model is not suitable to match the actual laser weld profile accurately. Furthermore, fiber lasers are widely recognized to result in good-quality laser beam output, a narrower weld zone, less distortion, and high process efficiency, compared with other types of lasers (such as CO2, Nd : YAG, and diode lasers). At present, there are few heat source models for fiber laser welding. Most of researchers evaluate the weld profile only by the bead width and depth of penetration, which is not suitable for the laser keyhole welding nail-like profile. This paper reports an experimental study and FEA simulation of fiber laser butt welding on 1 mm thick A304 stainless steel. A new heat source model (cylindrical and cylindrical) is established to match the actual weld profile using Marc and Fortran software. Four bead geometry parameters (penetration depth, bead width, waist width, and depth of the waist) are used to compare between the experimental and simulation results. The results show that the heat source model of cylindrical and cylindrical can match the actual shape of the fiber laser welding feasibly. The error range of the penetration depth, bead width, waist width, and depth of the waist between experimental and simulation results is about 4.1 ± 1.6%, 2.9 ± 2.0%, 13.6 ± 7.4/%, and 18.3 ± 8.0%, respectively. In addition, it is found that the depth of penetration is more sensitive to laser power rather than bead width, waist width, and depth of the waist. Welding speed has a similar influence on the depth of penetration, weld width, waist width, and depth of the waist.